Kapasitas Antioksidan Etlingera doliiformis: Jahe-jahean Endemik Sulawesi - Hurria (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2023)
Zingiberaceae is an aromatic plant that has the potential to produce essential oils. One of the species is Elingera doliiformis. Etlingera doliiformis A.D. Poulsen is an endemic species to Sulawesi from the Zingiberaceae family. This study is the first to examine the antioxidant potential of E. doliiformis. The aim of this research is to obtain the antioxidant capacity value of the endemic plant of Sulawesi, namely E. doliiformis. The plant materials used are leaves and flowers. Antioxidant capacity analysis was carried out using the DPPH (1,1-diphenyl-1-picrylhydrazyl) method. The vitamin C antioxidant test was carried out by dissolving 20 mg of vitamin C in 100 ml of 96% ethanol. The antioxidant activity of E. doliiformis flowers and leaves was determined using the DPPH test. The percentage of inhibition in flowers was higher than in leaves, although the difference was not significant. The results of the analysis of the antioxidant capacity of Etlingera doliiformis leaves and flowers showed high antioxidant potential. This potential can be used as a development in the pharmaceutical industry in the future.